Advanced research directions in gravitational wave detectors - Ivan P. Ohrymenko; Nikolai N. Kolchevsky; Pavel P. Petrov (Физика волновых процессов и радиотехнические системы, 2021)
The general principles of gravitational waves detection are considered in this paper. Current gravitational wave detectors represent modernized Michelson interferometer – LIGO-detector. Reduction of vibrations in the system and high stabilization of the reflective mirrors is one of the technical problem of the LIGO. It is proposed to study the features of the LIGO-detector with movable mirrors. The software simulating the operation of the LIGO and providing an opportunity to study its characteristics and capacity is developed and named «LIGO-RM». The primary goal of the modelling is to study the signal of the gravitational waves detector with oscillating mirrors. The «LIGO-RM» contains graphic user interface (GUI) that provides interactive control of mirrors movement nature and monitoring of detector signal change. The software simulates the presence of gravitational wave of a requested type and makes it able to monitor its effect on the operation results of the LIGO interferometer in interactive mode or as a numerical outcome. A range of numerical experiments is conducted and the signals on the detector with and without mirrors oscillations are shown. The results of calculations and a possibility of the registration of the gravitational waves using the LIGO-detector with movable mirrors are discussed.